A new species of Abacarus (Acari: Prostigmata: Eriophyidae) damaging sugarcane, Sacharrum officinarum L., from Costa Rica—the first eriophyoid mite described with a tibial seta on leg II DENISE NAVIA (Brazil), CARLOS H. W. FLECHTMANN (Brazil), EVERT E. LINDQUIST (Canada) & HUGO AGUILAR (Costa Rica) - Navia, Denise; Flechtmann, Carlos H.w.; Lindquist, Evert E.; Aguilar, Hugo (Zootaxa, 2011)
A new species of eriophyoid mite, belonging in the genus Abacarus Keifer (Eriophyidae), causing damage to sugarcane, Saccharum officinarum L. (Poaceae), in Costa Rica is illustrated and described. Abacarus doctus n. sp. is the only eriophyoid species recorded so far with a tibial seta (l¢) on the second pair of legs, an unexpected characteristic observed for the first time in the superfamily Eriophyoidea. Remarks on the phylogenetic and taxonomical aspects related to the presence of this seta are presented. Damage symptoms caused by this mite are presented as well as a key for Abacarus species described from sugarcane. In addition, the need to apply biosecurity procedures during sugarcane germplasm exchange to avoid dissemination of the new mite species is discussed.